Exploring The Theme Of Cultural Identify In R.K.Narayan’s Swami And Friends - Chetnaba Rajput; Jaiminibbahen G Chaudhari (Elementary Education Online, 2023)
This research seeks to examine the theme of cultural identity in R.K. Narayan’s classic novel, Swami and Friends. Set in the fictional town of Malgudi in British India, the story revolves around the lives of young Swaminathan and his friends, highlighting their experiences as they grapple with complex issues of tradition, modernity, and colonial influence. Through a close, analytical reading of the novel, this paper endeavors to explore how the characters navigate their evolving cultural identities amidst socioeconomic and political changes. Furthermore, it delves into R.K. Narayan’s portrayal of Indian culture and society, offering insight into the values and tensions that defined India during this period. By dissecting key narrative elements and character arcs, this investigation reveals how Swami and Friends serves as both a vivid snapshot of a bygone era and a timeless study of cultural identity formation in a rapidly changing world. The aim of this research paper is to examine the theme of cultural identity in R.K. Narayan’s Swami and Friends and how it reflects the socio-cultural milieu of pre-independence India. The novel, set in the fictional town of Malgudi, serves as a microcosm for India during this period and provides insight into the ways cultural identity is negotiated, contested, and reaffirmed amidst forces seeking change.